Precise evaluation method for the stability analysis of multi-scale slopes. (October 2020) - Yin, Xiangjie; Lin, Hang; Chen, Yifan; Wang, Yixian; Zhao, Yanlin
Slope stability analysis is a multi-scale problem. Typically, owing to the distinctions of slope scales (e.g., slope height or slope angle) in practical engineering, the stability calculation results of slopes with various scales from numerical methods inevitably exhibit different computational precision levels in the case of identical computational grids, and therefore the stability results of different slopes cannot be compared. To achieve equal accuracy stability analysis for multi-scale slopes, this study establishes numerical models of slopes with various scales as well as different grid shapes and sizes to conduct stability analysis. The results show the following: (a) a positive correlation relationship exists between the safety factor of the slope and the scaling factor, which is defined as the ratio of the grid size to the slope height; (b) the definition of the refined safety factor is given, representing the safety factor that corresponds to the infinitesimal grid size and eliminating the computational error of slope stability analysis caused by grid size or shape; (c) on this basis, embarking on the composite influence of multiple scales of slope on stability analysis, the study proposes a simplified treatment method suitable for evaluating the refined safety factor of the multi-scale slopes, which is verified as valid and feasible by some examples.